Towards an Inclusive Pedagogical Culture: Experiences from University Practice - Fernández-Fernández, Iliana María (2016)
In this paper, we deal with conceptual and methodological elements to develop the pedagogical inclusive competence of the professors of higher education in Ecuador. We analyze the current conceptions and the main drawbacks related to the inclusion process in the university environment nowadays. We support a theoretical procedural model, and from the practical standpoint, we implemented the methodological procedures structured in a map of processes to reach an inclusive formative process. The main results are given in the development of the pedagogical inclusive competence and the increase of the inclusion culture at the university, and revealed in the improvement of university curriculum from an inclusive approach, the betterment of the physical and technological infrastructure, the permanent upgrading of professors and putting into practice policies of affirmative action.